Processing, Nutrients, Market Access, and Pumpkin Rice Acceptance - Haryono, Haryono (West Science Social and Humanities Studies, 2024)
This study investigates the effects of processing techniques, nutrient content, and market accessibility on consumer acceptance of pumpkin analogue rice in Indonesia. As consumer demand for healthier and more sustainable food alternatives grows, understanding the key factors driving acceptance of innovative products like pumpkin analogue rice is critical. Using a quantitative approach, data were collected from 90 respondents through structured questionnaires and analyzed with SPSS version 25. The results reveal that processing techniques, nutrient content, and market accessibility significantly influence consumer acceptance, with nutrient content having the strongest impact. The findings suggest that optimizing processing methods, emphasizing health benefits, and improving market accessibility are essential for increasing the adoption of pumpkin analogue rice. This study provides practical insights for food producers and marketers seeking to promote healthier food alternatives in emerging markets.